Optimizing Packet Loss in Mobile IP Wireless Network Handover Performance Using Particle Swarm Optimization: The Role of Overlap Area Effectiveness - Mohamed Koum; Mohamed Hmadi (AlQalam Journal of Medical and Applied Sciences, 2026)
The rapid development of wireless technologies has led to a shift towards total mobility. Mobile IP provides mobility to mobile users and terminals as they change their point of attachment during handovers from a previous wireless access network to a new access network. This mobility is managed within the network layer through Mobile IP extensions, where mobile connectivity is supported while the MN is roaming between different wireless access networks. However, there are still several technical barriers, such as long handover periods and packet loss, that need to be overcome before the wide deployment of the Mobile Internet. In applications involving real-time traffic in IP wireless networks, mobile IP provides reliable access to the Internet. Mobile IP, is a network layer routing protocol, which was designed by the IETF (Internet Engineering Task Force) to provide solutions to the requirements of mobile computing. However, there are still many technical obstacles that must be overcome before Mobile IP can be widely deployed. Moreover, since mobility performance is the outcome of the cooperation of different layers, merely focusing on the network layer performance is not sufficient. In other words, the operation of Mobile IP depends heavily on lower-layer mechanisms and has direct implications for upper-layer performance. Therefore, in this paper, we optimize the number of packets lost based on the overlap area width in Mobile IP handover using Particle Swarm Optimization (PSO). Avoid losses of information during handover in Mobile IP networks. In this paper, we optimized the performance of the system using the PSO algorithm to improve the overall IP mobility performance. This paper focuses on the network handover mobility protocols and proposes enhancements to Mobile IP. The optimization schemes using MATLAB on the PSO Algorithm. Therefore, cross-layer analysis and design are necessary to improve the overall IP mobility performance. This paper focuses on the network layer mobility, proposes enhancements to Mobile IP, analyzes the impact that link layer mechanisms cause to IP mobility performance, and examines the implications of IP mobility on the transport layer, and concerns about the packet loss of information during handover. These occur during the movement from one point to another to achieve seamless mobile computing in a heterogeneous wireless access environment.